MSMEs Business Continuity Competitiveness during Post-Pandemic from the Lens of Disaster Recovery Business Planning Theory Approach - Maria Imelda Novita Susiang; Masydzulhak Djamil; Ahmad Badawi Saluy; Indra Siswanti (Universitas Mercu Buana, 2022)
2020 is the most difficult year in the start-up world due to the Covid-19 pandemic existed since the end of 2019 which forced every effort to turn the direction of strategy. Not a few also experience a crisis in the time of pandemic, so some companies have laid off their employees to reduce the burden of financing. The business sectors most affected are the commercial aviation, travel, oil and gas, automotive and banking sectors. But the business of the MSME sector is also affected due to the availability of raw materials and social restriction regulations. By applying the Action Research methodology from the literature study of post-pandemic phenomena, the study used a compilation data source to support this writing literature research. The focus of this writing is the MSME sector businesses that are still operating in the post-Covid-19 pandemic. Almost all business people in the MSME sector experienced a very drastic decrease in sales turnover, experiencing various marketing and sales constraints, as well as product distribution. Some business actors in the MSME sector are trying to maintain their business or business in the middle until after the Covid-19 pandemic by following government rules and health and security protocols with various efforts observed (observe), identified (to orient), make decisions (decide), and re-activity (to act) by continuously observing, identifying, making decisions, and acting continuously in one unconstrained cycle time. This study employs and implements an OODA loop or cycle. The concept of OODA loop is the concept of repeated analysis to determine the decision of a problem. OODA stands for Observe, Orient (problem identification), Decide (quick decision making), and Act (immediate action). The term cycle or loop comes from this concept because every process repeats until decisions taken are effective and able to have a significant impact in dealing with problems. For this reason, it is recommended that every business actor can try this method as a solution to the challenge of overcoming the economic crisis caused by COVID-19 through the OODA loop.